Reel pleasures : cinema audiences and entrepreneurs in twentieth-century urban Tanzania / Laura Fair. - Fair, Laura (New African histories series., 2018)
Reel Pleasures brings the world of African moviehouses and the publics they engendered to life, revealing how local fans creatively reworked global media-from Indian melodrama to Italian westerns, kung fu, and blaxploitation films-to speak to local dreams and desires. In it, Laura Fair zeroes in on Tanzanians' extraordinarily dynamic media cultures to demonstrate how the public and private worlds of film reception brought communities together and contributed to the construction of genders, generations, and urban citizenship over time. Radically reframing the literatures on media exhibition, distribution, and reception, Reel Pleasures demonstrates how local entrepreneurs and fans worked together to forge the most successful cinema industry in colonial sub-Saharan Africa. The result is a major contribution to the literature on transnational commodity cultures.